The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmats.2021.679682
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pre-Oxidation on High Temperature Oxidation and Corrosion Behavior of Ni-Based Aluminide Coating in Na2SO4 Salt at 1050°C

Abstract: Aluminide coating is prepared on K438 Ni-based superalloy by pack cementation. The hot corrosion test of as-received and pre-oxidation aluminide coating in Na2SO4 salt are carried out at 1050°C. The coating morphologies, phase composition, and corrosion products are characterized by XRD, SEM, EDS, and TEM. The conclusion is that the pre-oxidation aluminide coating has excellent hot corrosion properties. After hot corrosion, the oxide scale of pre-oxidation aluminide coating is the thinnest and maintains good i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…In recent years, through studying the influence of pre-oxidation on the high-temperature oxidation and heat resistance corrosion properties of the coating, Yang [ 9 ] found that a Pt-Al-coated sample can form a continuous and dense Al 2 O 3 film after pre-oxidation treatment, which can effectively prevent molten salt from directly entering the material surface, and the pre-oxidized samples did not indicate internal oxidation or a vulcanization phenomenon. In the process of a hot corrosion experiment, the oxide film formed on the surface of the pre-oxidized Al-Si coating is thin and maintains good integrity, but the structure of the oxide film formed fluctuates greatly, indicating that the oxide film grows toward the inner layer of the coating during the process of oxidation dissolution [ 10 , 11 ]. Gao Bo et al [ 12 ] studied the influence of oxidation on the high-temperature oxidation and hot corrosion behavior of Co-Al-W-based superalloy and found that, when the alloy pre-oxidized at 950 °C under normal oxygen, partial pressure was oxidized at 1000 °C, the oxidation products fell off less, the oxidation mass gain was slowed down and the oxidation resistance of the alloy was improved.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, through studying the influence of pre-oxidation on the high-temperature oxidation and heat resistance corrosion properties of the coating, Yang [ 9 ] found that a Pt-Al-coated sample can form a continuous and dense Al 2 O 3 film after pre-oxidation treatment, which can effectively prevent molten salt from directly entering the material surface, and the pre-oxidized samples did not indicate internal oxidation or a vulcanization phenomenon. In the process of a hot corrosion experiment, the oxide film formed on the surface of the pre-oxidized Al-Si coating is thin and maintains good integrity, but the structure of the oxide film formed fluctuates greatly, indicating that the oxide film grows toward the inner layer of the coating during the process of oxidation dissolution [ 10 , 11 ]. Gao Bo et al [ 12 ] studied the influence of oxidation on the high-temperature oxidation and hot corrosion behavior of Co-Al-W-based superalloy and found that, when the alloy pre-oxidized at 950 °C under normal oxygen, partial pressure was oxidized at 1000 °C, the oxidation products fell off less, the oxidation mass gain was slowed down and the oxidation resistance of the alloy was improved.…”
Section: Introductionmentioning
confidence: 99%